Sex Education for Elementary School Children in Indonesia; Bibliometric Analysis in 2021-2024 - Witasari, Rinesti (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2024)
This study provides an overview of the analysis of sex education trends in elementary school children in Indonesia for the 2021-2024 period using bibliometric analysis, aiming to identify research gaps that have not been widely studied and provide recommendations for further research. The method used is systematic literature review by utilizing Vosviewer as a meta-data analysis tool. Data was obtained from a POP search on Google Scholar 2021-2024 with the keyword